Incidence of Respiratory Virus-Associated Pneumonia in Urban Poor Young Children of Dhaka, Bangladesh, 2009–2011 - Homaira, Nusrat (Public Library of Science, 2012)
BACKGROUND: Pneumonia is the leading cause of childhood death in Bangladesh. We conducted a longitudinal study to estimate the incidence of virus-associated pneumonia in children aged <2 years in a low-income urban community in Dhaka, Bangladesh. METHODS: We followed a cohort of children for two years. We collected nasal washes when children presented with respiratory symptoms. Study physicians diagnosed children with cough and age-specific tachypnea and positive lung findings as pneumonia case-patients. We tested respiratory samples for respiratory syncytial virus (RSV), rhinoviruses, human metapneumovirus (HMPV), influenza viruses, human parainfluenza viruses (HPIV 1, 2, 3), and adenoviruses using real-time reverse transcription polymerase chain reaction assays. RESULTS: Between April 2009–March 2011, we followed 515 children for 730 child-years. We identified a total of 378 pneumonia episodes, 77% of the episodes were associated with a respiratory viral pathogen. The overall incidence of pneumonia associated with a respiratory virus infection was 40/100 child-years. The annual incidence of pneumonia/100 child-years associated with a specific respiratory virus in children aged <2years was 12.5 for RSV, 6 for rhinoviruses, 6 for HMPV, 4 for influenza viruses, 3 for HPIV and 2 for adenoviruses. CONCLUSION: Young children in Dhaka are at high risk of childhood pneumonia and the majority of these episodes are associated with viral pathogens. Developing effective low-cost strategies for prevention are a high priority.